2014
DOI: 10.1038/ncb3035
|View full text |Cite|
|
Sign up to set email alerts
|

RASSF1A–LATS1 signalling stabilizes replication forks by restricting CDK2-mediated phosphorylation of BRCA2

Abstract: Genomic instability is a key hallmark of cancer leading to tumour heterogeneity and therapeutic resistance. BRCA2 has a fundamental role in error-free DNA repair but also sustains genome integrity by promoting RAD51 nucleofilament formation at stalled replication forks. CDK2 phosphorylates BRCA2 (pS3291-BRCA2) to limit stabilizing contacts with polymerized RAD51; however, how replication stress modulates CDK2 activity and whether loss of pS3291-BRCA2 regulation results in genomic instability of tumours are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 60 publications
3
102
0
Order By: Relevance
“…Recollecting this evidence, we envisioned that, while Hippo kinases may be intertwined with cell cycle checkpoints and DNA damage repair effectors in TNBC, they prevalently operate in the context of the canonical Hippo machinery in HER2-driven BC. This is consistent with preclinical studies describing that key Hippo pathway components are targeted by the ATM/Chk2 and ATR/Chk1 pathways, [23][24][25][26] as well as with our previous findings describing a lower pCR rate in TNBC patients with elevated expression levels of DDR-linked biomarkers in their tumors. 16 Next, evidence that both estrogens, via G proteincoupled estrogen receptor (GPER), and HER2 via mechanotransduction, intersect the Hippo pathway corroborates the hypothesis of molecular subtype-dependent levels of Hippo pathway regulation in BC.…”
Section: Discussionsupporting
confidence: 79%
“…Recollecting this evidence, we envisioned that, while Hippo kinases may be intertwined with cell cycle checkpoints and DNA damage repair effectors in TNBC, they prevalently operate in the context of the canonical Hippo machinery in HER2-driven BC. This is consistent with preclinical studies describing that key Hippo pathway components are targeted by the ATM/Chk2 and ATR/Chk1 pathways, [23][24][25][26] as well as with our previous findings describing a lower pCR rate in TNBC patients with elevated expression levels of DDR-linked biomarkers in their tumors. 16 Next, evidence that both estrogens, via G proteincoupled estrogen receptor (GPER), and HER2 via mechanotransduction, intersect the Hippo pathway corroborates the hypothesis of molecular subtype-dependent levels of Hippo pathway regulation in BC.…”
Section: Discussionsupporting
confidence: 79%
“…RASSF1 controls genome stability in response to replication stress through activation of the Hippo pathway, which regulates phosphorylation of breast cancer 2 (BRCA2) and recruitment of RAD51 recombinase (RAD51) (42). The absence of RASSF1A led to chromosomal aberrations and increased genomic instability such as that seen in BRCA-mutant cells (42). Concordantly, a positive correlation between RASSF1A promoter methylation and increased copy number alteration has been shown in breast and lung cancer (43).…”
Section: Prediction Of Survival Outcomes In Other Cancer Types With Tmentioning
confidence: 69%
“…RASSF1 is a well-established tumor suppressor that is frequently inactivated in several cancers, including breast and lung cancer, by aberrant promoter methylation. RASSF1 controls genome stability in response to replication stress through activation of the Hippo pathway, which regulates phosphorylation of breast cancer 2 (BRCA2) and recruitment of RAD51 recombinase (RAD51) (42). The absence of RASSF1A led to chromosomal aberrations and increased genomic instability such as that seen in BRCA-mutant cells (42).…”
Section: Prediction Of Survival Outcomes In Other Cancer Types With Tmentioning
confidence: 99%
“…It was recently reported that extra centrosomes caused by cytokinesis failure activate LATS2, which in turn stabilizes p53 and inhibits YAP/TAZ transcriptional activity (Ganem et al 2014). LATS1 also interacts with CDK2 in response to genotoxic stress to restrict CDK2-mediated phosphorylation of BRCA2 and support RAD51 nucleofilaments, thereby maintaining genome fidelity during replication stalling (Pefani et al 2014). YAP, in complex with the transcription factor PKNOX1, has been shown to control S-phase temporal progression and genomic stability of retinal stem cells (Cabochette et al 2015).…”
Section: Cell Cyclementioning
confidence: 99%